Track-and-tune light field image sensor - Shen, ZeXiang (2014)
In this paper, we present a new technique for determining the angle of incident light using an image sensor. This technique makes use of two distinct pixel types for simultaneous coarse angle estimation and fine angle detection. A new type of pixel structure, the quadrature pixel cluster is introduced, which produces response that varies linearly with incident light angle. The proposed technique greatly reduces the overall sensor complexity and is very area efficient compared with the previous work on angle detection. The sensor is fabricated in 65-nm mixed-signal CMOS process and can accurately distinguish between angles in the range from -35° to +35°.